2004
DOI: 10.1074/jbc.m309376200
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Spacing of TATA Box Elements Are Critical for Accurate Initiation from the β-Phaseolin Promoter

Abstract: The ␤-phaseolin (phas) gene, which encodes one of the major seed storage proteins of P. vulgaris, is tightly regulated at the transcription level resulting in strict tissuespecific and spatial expression during embryonic development. The phas proximal promoter contains a complex arrangement of core promoter elements including three TATA boxes as well as several putative initiator elements. To delineate the respective contributions of the core promoter elements to transcription initiation we have performed site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…Evolutionary fate of rhizome-specific genes anaerobic genes (AAACAAA; Mohanty et al, 2005) showed significantly higher abundance in S. bicolor than the other species. The promoters of S. bicolor genes were enriched relative to those of O. sativa for three additional cis-elements, À300 element (Thomas and Flavell, 1990), À10 promoter element (Thum et al, 2001) and TATA box (Grace et al, 2004). By contrast, two promoters, polyA signal (O'Nell et al, 1990) and pro-or hypo-osmolarity element found in the promoter of proline dehydrogenase (Satoh et al, 2002) were more abundant in the promoters of S. bicolor than S. propinquum alleles.…”
Section: Evolutionary Fate Of Rhizome-specific Genesmentioning
confidence: 95%
See 1 more Smart Citation
“…Evolutionary fate of rhizome-specific genes anaerobic genes (AAACAAA; Mohanty et al, 2005) showed significantly higher abundance in S. bicolor than the other species. The promoters of S. bicolor genes were enriched relative to those of O. sativa for three additional cis-elements, À300 element (Thomas and Flavell, 1990), À10 promoter element (Thum et al, 2001) and TATA box (Grace et al, 2004). By contrast, two promoters, polyA signal (O'Nell et al, 1990) and pro-or hypo-osmolarity element found in the promoter of proline dehydrogenase (Satoh et al, 2002) were more abundant in the promoters of S. bicolor than S. propinquum alleles.…”
Section: Evolutionary Fate Of Rhizome-specific Genesmentioning
confidence: 95%
“…Five additional cis-acting regulatory elements, such as CRT/DRE motif (Xue, 2003), (CA) n element in storage protein genes (Ellerstrom et al, 1996), TATA box (Grace et al, 2004), the CCA1-binding element related to regulation by phytochrome (Wang et al, 1997), and pyrimidine box required for gibberellic acid (GA) induction (Cercos et al, 1999), were also more abundant in S. propinquum than either S. bicolor or O. sativa alleles (Table 3).…”
Section: Evolutionary Fate Of Rhizome-specific Genesmentioning
confidence: 99%
“…Several putative TATA boxes were found in OsNRT2.1, OsNRT2.2 and OsNRT2.4. TATABOX2 (Grace et al 2004) was found at −152 and at −124 in OsNRT2.1 and OsNRT2.2, respectively. TATABOXOSPAL (Zhu et al 2002) was found at −156 in OsNRT2.4.…”
Section: Information Of Osnrt2smentioning
confidence: 99%
“…Three TATA box sequences are located upstream from the mRNA cap at positions -28, -37 and -39. Slightom et al [25] postulated that the sequence at -28 was likely to be the most important in driving high expression from the phas promoter; this was later confirmed by Grace et al [40] who used an in vitro transcription system that revealed that the sequence and spacing of the TATA box elements are critical for accurate initiation from the -phaseolin promoter. The A+T content of the introns is similar to that in soybean proteins, but is considerably higher than those of non-plant species.…”
Section: Phaseolin Gene Structurementioning
confidence: 63%